Monuments Included in The Unesco List of Historical Cities of Uzbekistan - Usarov Jamoliddin Tolkinovich (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This article discusses the monuments included in the UNESCO list in the historical cities of Uzbekistan. There are five names of objects on the UNESCO World Heritage List in Uzbekistan. Four are included in the list according to cultural criteria - the historical centers of Khiva, Bukhara, Samarkand and Shakhrisabz, one according to natural criteria - the Western Tien Shan (Chatkal Reserve). At the stage of inclusion - more than 30 objects.